Basic Principles Of Arabic Language Teaching Methods - Nasiri (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2024)
There are three basic principles in teaching Arabic: priority in the presentation of teaching materials, correction and feedback, and the gradual principle in delivering material to students. Several steps are required in teaching Arabic to ensure successful and effective delivery: providing examples before explaining grammatical rules, providing examples of commonly used sentences, and providing sufficient motivation to express themselves through writing, speaking, and perhaps even facial expressions, so that students feel directly involved in the teaching process.There are two types of Arabic teaching methods: the traditional method, which focuses on "language as a culture of knowledge," so that learning Arabic means in-depth study of the intricacies of Arabic language science itself. The modern method, which focuses on the purpose of language as a means of communication in modern life, is essential.